Science and policy on endocrine disrupters must not be mixed: a reply to a "common sense" intervention by toxicology journal editors. - Bergman, Åke.; Andersson, Anna-Maria.; Becher, Georg.; van den Berg, Martin.; Blumberg, Bruce.; Bjerregaard, Poul.; Bornehag, Carl-Gustaf.; Bornman, Riana.; Brandt, Ingvar.; Brian, Jayne V.; Casey, Stephanie C.; Fowler, Paul A.; Frouin, Heloise.; Giudice, Linda C.; Iguchi, Taisen.; Hass, Ulla.; Jobling, Susan.; Juul, Anders.; Kidd, Karen A.; Kortenkamp, Andreas.; Lind, Monica.; Martin, Olwenn V.; Muir, Derek.; Ochieng, Roseline.; Olea, Nicolas.; Norrgren, Leif.; Ropstad, Erik.; Ross, Peter S.; Rudén, Christina.; Scheringer, Martin.; Skakkebaek, Niels Erik.; Söder, Olle.; Sonnenschein, Carlos.; Soto, Ana.; Swan, Shanna.; Toppari, Jorma.; Tyler, Charles R.; Vandenberg, Laura N.; Vinggaard, Anne Marie.; Wiberg, Karin.; Zoeller, R Thomas. (2016)
Abstract: The "common sense" intervention by toxicology journal editors regarding proposed European Union endocrine disrupter regulations ignores scientific evidence and well-established principles of chemical risk assessment. In this commentary, endocrine disrupter experts express their concerns about a recently published, and is in our considered opinion inaccurate and factually incorrect, editorial that has appeared in several journals in toxicology. Some of the shortcomings of the editorial are discussed in detail. We call for a better founded scientific debate which may help to overcome a polarisation of views detrimental to reaching a consensus about scientific foundations for endocrine disrupter regulation in the EU.; Keywords: Endocrine disrupting chemicals, Environment, Health, Precautionary principle, Regulatory toxicology.; Springer Open.